2019
DOI: 10.1002/hipo.23187
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of systems memory consolidation and reconsolidation

Abstract: In the mammalian brain, newly acquired memories depend on the hippocampus for maintenance and recall, but over time these functions are taken over by the neocortex through a process called systems memory consolidation. However, reactivation of a well-consolidated memory can return it to a hippocampus-dependent state. This is normally followed by a restoration of hippocampusindependence, a phenomenon known as systems memory reconsolidation. The neural mechanisms underlying systems memory consolidation and recon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…As we have speculated previously, these considerations suggest that destabilisation may not be an allor-nothing process, but proportional to the magnitude of the PE 'updating signal', an idea for which contemporary computational models of reconsolidation (Gershman et al, 2017;Helfer and Shultz, 2017;Osan et al, 2011) and empirical evidence (Reichelt and Lee, 2013) provide some support. Importantly, this relationship between PE and destabilisation need not be linear.…”
Section: Discussionmentioning
confidence: 57%
“…As we have speculated previously, these considerations suggest that destabilisation may not be an allor-nothing process, but proportional to the magnitude of the PE 'updating signal', an idea for which contemporary computational models of reconsolidation (Gershman et al, 2017;Helfer and Shultz, 2017;Osan et al, 2011) and empirical evidence (Reichelt and Lee, 2013) provide some support. Importantly, this relationship between PE and destabilisation need not be linear.…”
Section: Discussionmentioning
confidence: 57%
“…For reviews of reconsolidation research, see [22][23][24]. For a computational model of systems consolidation and reconsolidation, see [25].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the reconsolidation theory, it has been observed that the earlier the intervention is performed after memory retrieval, the weaker the memory trace will be reconsolidated (Helfer and Shultz 2019). For instance, MK801 impaired procedural memory reconsolidation when administered up to 90 min after retrieval and anisomycin caused passive-avoidance amnesia in mice when injected 30 min or less after memory reactivation (Judge and Quartermain 1982;Przybyslawski and Sara 1997).…”
Section: Discussionmentioning
confidence: 73%